Eastern Caribbean Currency Union : Staff Report for the 2006 Regional Discussions. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the 2006 Regional Discussions on the Eastern Caribbean Currency Union. Fiscal revenues have improved, but there has been only a modest improvement in the fiscal and debt positions. Tax revenues have strengthened with the uptick in economic activity, administrative efforts, and tax reforms. The financial system has been resilient, but additional efforts are needed to strengthen the supervisory framework in the face of emerging risks. Progress continues to be made in implementing the Financial Sector Assessment Program (FSAP) recommendations, but there is a need to ensure enforcement of the new regulatory framework.